Affective Temperaments, Panic Disorder and Their Bipolar Connections - Zsuzsanna Belteczki; Zoltan Rihmer; Sandor Rozsa; Julia Ujvari; Maurizio Pompili; Xenia Gonda; Péter Dome (Medicina, 2021)
Background and Objectives: The role of affective temperament in the genesis and outcome of major mood disorders is well studied, but there are only a few reports on the relationship between panic disorder (PD) and affective temperaments. Accordingly, we aimed to study the distribution of affective temperaments (depressive (DE); cyclothymic (CT); irritable (IRR); hyperthymic (HT) and anxious (ANX)) among outpatients with PD. Materials and Methods: Affective temperaments of 118 PD outpatients (80 females and 38 males) with or without agoraphobia but without any other psychiatric disorder at the time of inclusion were evaluated using the Temperament Evaluation of the Memphis, Pisa, Paris, and San Diego Autoquestionnaire (TEMPS-A) and compared with the affective temperament scores of control subjects. All patients were followed up for at least 1.5 years in order to detect the onset of any major affective disorders, substance use disorders and suicide attempts. Results: Among females, the dominant ANX and DE temperaments were four and three times as common as in a large normative Hungarian sample (for both cases p < 0.01). Among male PD patients, only the dominant DE temperament was slightly overrepresented in a non-significant manner. Females with PD obtained significantly higher scores on ANX, DE and CT subscales of the TEMPS-A, whereas males with PD showed significantly higher scores on ANX, DE and HT temperament subscales compared with the members of a large normative Hungarian sample and also with a gender- and age-matched control group. During the follow-up, newly developed unipolar major depression and bipolar spectrum (bipolar I or II and cyclothymic) disorders appeared in 64% and 22% of subjects, respectively. Conclusions: Our preliminary findings suggest that a specific, ANX-DE-CT affective temperament profile is characteristic primarily for female patients, and an ANX-DE-HT affective temperament profile is characteristic for male patients with PD, respectively. These findings are in line with expectations because PD is an anxiety disorder par excellence on the one hand, whereas, on the other hand, it is quite frequently comorbid with mood (including bipolar) disorders.